2017
DOI: 10.1016/j.drugalcdep.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, reasons, perceived effects, and correlates of medical marijuana use: A review

Abstract: Background The use of marijuana for medical purposes is now legal in some U.S. states and other jurisdictions, such as Canada, and Israel. Despite the widespread legalization of medical marijuana globally, there is limited information on patterns and correlates of medical marijuana use (MMU). We conducted a literature review to assess prevalence, reasons, perceived effects, and correlates of MMU among adolescents and adults. Methods We searched peer-reviewed articles in English between January 1996 and Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 58 publications
(151 reference statements)
5
92
0
1
Order By: Relevance
“…In general, pain or chronic pain seems to be the major reason for patients to use medicinal cannabis. The abovementioned review revealed that 30-87% of patients in different patient populations claiming to use cannabis for medicinal purposes report pain or chronic pain relief as the reason for medicinal cannabis use; 15 the results were based on nine articles from the United States, Israel, and the UK. [16][17][18][19][20][21][22][23][24] Based on these nine heterogeneous studies, plus one additional study using data from a dispensary in California, 25 we empirically estimate a median of 78% (95% CI: 31-82.6) of patients reporting pain as a reason for cannabis use among these diverse populations.…”
Section: Modern Pharmacy Paradox Of Cannabis and Pharmaceutical Cannamentioning
confidence: 99%
“…In general, pain or chronic pain seems to be the major reason for patients to use medicinal cannabis. The abovementioned review revealed that 30-87% of patients in different patient populations claiming to use cannabis for medicinal purposes report pain or chronic pain relief as the reason for medicinal cannabis use; 15 the results were based on nine articles from the United States, Israel, and the UK. [16][17][18][19][20][21][22][23][24] Based on these nine heterogeneous studies, plus one additional study using data from a dispensary in California, 25 we empirically estimate a median of 78% (95% CI: 31-82.6) of patients reporting pain as a reason for cannabis use among these diverse populations.…”
Section: Modern Pharmacy Paradox Of Cannabis and Pharmaceutical Cannamentioning
confidence: 99%
“…Prior findings revealed that medical marijuana users tended to have more anxiety disorder, but less alcohol use disorder than recreational marijuana users (Compton et al, 2017; Park and Wu, 2017). However, differences in patterns of other SUDs and treatment seeking have not been systematically examined in a large representative sample.…”
Section: Introductionmentioning
confidence: 99%
“…The original 25-item questionnaire includes five subscales: social (e.g., “to celebrate a special occasion with friends”), coping (e.g., “because it helps me when I'm depressed or nervous”), enhancement (e.g., “because it gives me a pleasant feeling”), conformity (e.g., “to fit in with a group I like”), and expansion (e.g., “to understand things differently”). In this study, 6 new items were added to create a subscale assessing medical motivations for use: “to relieve symptoms of HIV or other chronic illness,” “to aid relaxation,” “to relieve pain,” “to obtain energy,” “to decrease nausea,” and “to increase appetite.” These items were selected based on prior research showing that these are common medical benefits of marijuana use reported in HIV+ samples [18,25-27] and non-HIV samples [28-30]. The items we selected share some overlap with a new health subscale created for an adolescent sample, though this study was not published until after data collection for our project was completed [31].…”
Section: Methodsmentioning
confidence: 99%